A Study on the Current Status and Librarian Perception of Readers’ Advisory in Korean University Libraries: A focus on Leisure Reading - Jeong, Dae-Keun (International Journal of Knowledge Content Development & Technology, 2020)
This study attempted to establish the role of university libraries for leisure reading by identifying the current status of university libraries about leisure reading, which is a part of the reading support service and by investigating and analyzing the university library librarian’s perception of the necessity of leisure reading. To this end, a survey was conducted on university libraries. As a result of the survey, 78% of university libraries were conducting leisure reading, and 72% of them provided separate space. Separate manpower was provided only in 30% of libraries, and book lists were provided mainly by best sellers. Regarding the need for leisure reading (4.28) and the role of university libraries (4.32), librarians responded that it was a necessary service for university libraries, and university library librarians that currently provide spaces and programs were more aware of the need. URL: http://ijkcdt.net/xml/27017/27017.pdf